2007
DOI: 10.2171/jao.38.280
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified Method for Estimating Intensity of the Lingering Cigarette Odor

Abstract: The method developed to analyze the components of cigarette odors is capable of quantitatively evaluating lingering odor using a simple procedure. The odor intensity is then estimated by condensing the gas evaporated from curtain material previously exposed to cigarette odors and subsequently analyzing the gas with gas chromatograph mass spectrometry. The lingering odor has been confirmed to contain aldehyde, olefin, heterocyclic and heteroaromatic compounds. After confirming the linear correlation between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In particular, the gas detector tube can quickly determine the odor whenever it is required. Based on previous studies [11] and the results of this experiment, ammonia is considered a suitable gas detector tube type, but there are some problems with the lower limit of quantifica-tion; therefore, we believe that it would be best used in approximating the residual odor prior to a precise analysis. If two different odor-level standard gases can be used for the calibration of the regression curve for each monitor, it is possible to use them as measuring instruments for thirdhand smoke odor.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In particular, the gas detector tube can quickly determine the odor whenever it is required. Based on previous studies [11] and the results of this experiment, ammonia is considered a suitable gas detector tube type, but there are some problems with the lower limit of quantifica-tion; therefore, we believe that it would be best used in approximating the residual odor prior to a precise analysis. If two different odor-level standard gases can be used for the calibration of the regression curve for each monitor, it is possible to use them as measuring instruments for thirdhand smoke odor.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding the gas detector tube, we decided to use an ammonia detector, as opposed to a pyridine detector, because, based on the results of Sample A (Figure 2), ammonia has a longer measurement time than pyridine. Previous studies have also reported that ammonia tends to adhere to curtain material, meaning it may potentially be more detectable [11]. 105SD has a higher coefficient of determination than No.3L; therefore, it was used in subsequent experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation